ISOLATION, CLONING, AND CHARACTERIZATION OF phbA, phbB, and phbC GENES IN BIOSYNTHESIS OF POLY-(R)-3-HYDROXYBUTYRATE - Ode Sri Rizki, Wa
The increase in population is directly proportional to the use of plastic. The accumulation of large amounts of synthetic waste can cause environmental pollution because it is difficult to degrade. One effort to overcome plastic waste is the use of biodegradable plastic or commonly called bio plastics. Poly(R) -3-hydroxybutyrate (PHB) is one of the bio plastics synthesized and accumulated by bacteria intracellular as an energy reserve. PHB bio synthetic pathways in bacteria involve 3 genes, namely phbA (encodes acetyl-CoA-acetyltransferase), phbB (encodes acetoacetyl-CoA reductase), and phbC encodes PHB synthase). Production of PHB from Halomonas elongata bacteria is still quite low at around 20%. Therefore, this study aims to isolation and cloning of three genes that play a role in PHB bio synthesis to improve productivity of PHB. This study began with a qualitative test of PHB producing bacteria. Halomonas elongata BK-AG25 gives positive results as PHB producing bacteria. The phbA, phbB, and phbC genes have been successfully amplified from genome Halomonas elongata BK-AG25 using each pair of primers that have been designed based on the similarity of gene sequences to some halomonas species. The three DNA fragments were cloned into the pGEM-T Easy vector and transformed into E.coli TOP10. Recombinant colonies were selected based on white-blue selection and analyzed based on colony PCR, size screening plasmid , and re PCR. The results of the analysis of recombinant colonies were confirmed based on the results of nucleotide sequence determination. The phbA, phbB and phbC fragments are aligned using Seqman and the sequence is determined using BLASTN. The order of phbA, phbB, and phbC has similarities of 97%, 98% and 99% with the genome Halomonas elongata DSM 2581 (Access No. FN 869568.2). The amino acid PhbA sequence was 74% similar to acetyl-CoA acetyltransferase (Access No. WP013333885.1). PhbB amino acid sequence has a similarity of 99% with acetoacetyl-CoA reductase (Access No. WP065241591.1). While the amino acid PhbC sequence has a similarity of 99% with PHB synthase (Access No. WP013333150.1). The results of the analysis of amino acids PhbA, PhbB, and PhbC using ExPASy showed that all dominanted by non polar aliphatic amino acids. The results of the secondary structure analysis of PhbA, PhbB, and PhbC using SAS (Sequence Annotated by Structure) show that the three proteins are dominated by coil/turn structure. The results of the analysis of tertiary structures using SWISS Model and I-TASSER indicate that PhbA, PhbB, and PhbC have folds of ?/?. Catalytic residues for PhbA were Cys96, and Ser360, catalytic residues for PhbB were Asn113, Ser141, Gln151, Tyr154, and Lys158 and catalytic residues for PhbC were Cys330, Asp485 and His513. It can be concluded that the phbA, phbB, and phbC genes have been successfully cloned to the Easy pGEM-T vector.